Penerapan Model PBL untuk Meningkatkan Keaktifan dan Hasil Belajar Bahasa Indonesia pada Siswa Kelas IV SD - Indaryati, Oktavia Nur; Abduh, Muhammad; Lestari, Sri (FONDATIA, 2024)
Low learning results in Indonesian language classrooms, caused by students who were less active during the learning process, served as the driving force for this study. The reason is that traditional, less innovative teaching strategies still need more work from teachers than from students. To solve these issues, a problem-based learning approach is employed. This study attempts to boost the effectiveness and activity of learning Indonesian by utilizing the PBL approach. Classroom action research is a sort of research that is conducted in two cycles. 26 fourth-grade students from SDIT Nur Hidayah Surakarta participated in this study. Data is gathered through tests and observations, organized, presented, and analyzed to conclude. According to the study's findings, student activity rose from 52.47% before the action to 85.47% following it. In addition, learning outcomes improved from 72.69% before the activity to 92.11% after it. It was determined that during the first semester of the 2023–2024 academic year, class IV students at SDIT Nur Hidayah Surakarta increased their level of activity and had better learning results when using the PBL approach.